Enhancing TOEFL Performance and Student Motivation through Integrated Flipped and Gamified Learning in Online Settings - Safnil Arsyad; Budi Waluyo; Ira Maisarah (Human Behavior and Emerging Technologies)
In the evolving landscape of education, the integration of flipped and gamified learning into online English courses has remained a complex and underexplored terrain. To address this knowledge gap, our study designed and implemented an innovative hybrid pedagogical model, seamlessly blending flipped and gamified learning principles into the context of online TOEFL (Test of English as a Foreign Language) instruction. The study, conducted within a public university in Bengkulu Province, Indonesia, included 27 carefully selected research participants (11.1% male, 88.9% female) from a population of 80 third-year undergraduate English majors, employing purposive convenient sampling techniques to ensure diversity representation. Our comprehensive data collection encompassed pre- and post-TOEFL assessments, surveys, and reflective essays, with qualitative data subjected to thematic analysis and quantitative data analyzed through descriptive statistics, nonparametric Wilcoxon rank tests, and Spearman’s correlation analysis. The results unveiled a multifaceted landscape, showing improvements in student enjoyment and motivation alongside increased anxiety. However, the intervention demonstrated significant enhancements in TOEFL listening, reading, and overall scores, although structure and written expression remained largely unchanged. Intriguingly, while heightened enjoyment correlated with increased motivation, emotional variables displayed no significant correlation with TOEFL posttest scores. These findings carry profound implications for TOEFL preparation, student motivation, and the management of classroom diversity in online learning settings.